2020
DOI: 10.1136/tobaccocontrol-2019-055318
|View full text |Cite
|
Sign up to set email alerts
|

PMI’s heated tobacco products marketing claims of reduced risk and reduced exposure may entice youth to try and continue using these products

Abstract: ImportancePhilip Morris International (PMI) is seeking Food and Drug Administration’s (FDA) authorisation to market IQOS as a modified risk tobacco product and to make marketing claims of reduced risk and reduced exposure. Such claims may be misunderstood by youth, thereby increasing their risk for tobacco initiation.ObjectiveTo assess youth (mean age 19.3, SD=1.7) understanding and perceptions of PMI’s proposed consumer marketing claims of reduced risk and reduced exposure, we embedded a randomised controlled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 31 publications
3
26
0
Order By: Relevance
“…We can suspect that the tobacco industry's marketing efforts on the health effect of tobacco use are targeted strictly to smokers to discourage them from quitting smoking. Moreover, a relatively high percentage of respondents (>20%), who declared that e-cigarettes and HTPs are less harmful than traditional cigarettes may result from the fact that these products are aggressively marketed in the EU [28].…”
Section: Discussionmentioning
confidence: 99%
“…We can suspect that the tobacco industry's marketing efforts on the health effect of tobacco use are targeted strictly to smokers to discourage them from quitting smoking. Moreover, a relatively high percentage of respondents (>20%), who declared that e-cigarettes and HTPs are less harmful than traditional cigarettes may result from the fact that these products are aggressively marketed in the EU [28].…”
Section: Discussionmentioning
confidence: 99%
“…This is important given that harm reduction appears to be conditional on completely switching (and not dual product use) [ 11 ]. However, the limited research on this wording so far is somewhat mixed on whether consumers understand what it means [ 12 , 13 , 14 ]. Camel’s proposed ads also include modified exposure claims (e.g., stating that “scientific studies have shown that Camel Snus contains less of the harmful chemicals than cigarette smoke”) as well as several statements attempting to connect the role of combustion with modified risk and exposure (e.g., “no smoke = less risk”).…”
Section: Introductionmentioning
confidence: 99%
“…First, due to less harshness than combustible cigarettes and kid-friendly flavors, HTPs can be easier to initiate and more appealing to youth who do not use or lightly use nicotine, and facilitate persistent and frequent use. 39 , 40 , 41 Second, despite no flames, the I Quit Original Smoking (IQOS) tobacco product sticks (Philip Morris International), with similar ingredients to cigarettes, are always charred because of pyrolysis and generate volatile and semi-volatile toxicants as in cigarette smoke, challenging the claim of “heat but not burn.” 4 Third, harmful constituents are increasingly confirmed in HTPs. Many harmful and potentially harmful substances in the aerosol of IQOS are more than 50% higher than cigarette smoke, such as glycerol, α,β-unsaturated carbonyl compounds, 1,2-dicarbonyl compounds, furans and epoxides.…”
Section: Discussionmentioning
confidence: 99%